The impact of the COVID-19 pandemic on addressing common barriers to pharmacy-based point-of-care testing. (3rd August 2021) - Klepser, Donald G.; Klepser, Nicklas S.; Adams, Jennifer L.; Adams, Alex J.; Klepser, Michael E.
ABSTRACT: Introduction : Pharmacy-based point-of-care testing has long had the potential to improve patient access to timely care, but adoption has been slowed by financial and regulatory barriers. The COVID-19 pandemic reduced or temporarily eliminated many of the barriers to pharmacy-based testing. This review examines how the changes brought on by may impact pharmacy-based testing after the pandemic. Areas covered : This review searched peer-reviewed, lay, and regulatory literature to explore the implementation of pharmacy-based COVID-19 testing. This includes a review of regulatory and financial changes that removed barriers to testing. Additionally, it reviews the literature related to the growth of pharmacy-based testing. Expert opinion : It is clear that the COVID-19 pandemic created an awareness and opportunity for pharmacy-based point-of-care testing. The changes made in response to the pandemic have the potential to increase the role of pharmacy-based testing, but additional regulatory changes and wider pharmacy adoption are still needed to maximize the value of such services.